Multiperiod Location–Allocation Optimization of Construction Logistics Centers for Large-Scale Projects in Complex Environmental Regions - Hao Shen; Jin Zhang; Wenjie Sun; Wenguang Yang; Guoqi Li (Buildings)
As an efficient management pattern to improve logistics efficiency through intensive management of construction materials, construction logistics centers (CLCs) have received active attention from academics and practitioners. However, the CLC location–allocation problem, which considers periodic demand and transportation risk, has not been adequately solved. This work provides an approach to integrating transportation path risk into multiperiod CLC location–allocation optimization for large-scale projects in complex environmental regions. For this purpose, this paper formulates a hybrid non-linear integer planning model to define this location–allocation problem and minimize the total cost of construction logistics and transportation risk. The model also incorporates critical features from realistic scenarios, including CLC’s service coverage, capacity constraints, and minimum utilization limits. We have designed an NSGA-II based on endocrine hormone regulation (EHR-NSGA-II) to solve the model. Finally, a large-scale railroad construction project in complex environmental regions is used as an example to prove the effectiveness of the model and algorithm. Compared with the single-period model, the multiperiod model designed in this paper provides a total cost reduction of 8.11% for the CLC location–allocation scheme. In addition, analyzing several key parameters provides valuable insights for managers to design more reliable construction logistics networks.